Oryza tag line, a phenotypic mutant database for the génoplante rice insertion line library - Larmande, Pierre; Gay, C; Lorieux, Mathias; Perin, C.; Bouniol, M; Droc, Gaëtan; Sallaud, C; Pérez, P.; Barnola, I; Biderre-Petit, Corinne; Martin, J.; Morel, Jean-Benoit; et al. (Oxford University Press, 2008)
To organize data resulting from the phenotypic characterization of a library of 30 000 T-DNA enhancer trap (ET) insertion lines of rice (Oryza sativa L cv. Nipponbare), we developed the Oryza Tag Line (OTL) database (http://urgi.versailles.inra.fr/OryzaTagLine/). OTL structure facilitates forward genetic search for specific phenotypes, putatively resulting from gene disruption, and/or for GUSA or GFP reporter gene expression patterns, reflecting ET-mediated endogenous gene detection. In the latest version, OTL gathers the detailed morpho-physiological alterations observed during field evaluation and specific screens in a first set of 13 928 lines. Detection of GUS or GFP activity in specific organ/tissues in a subset of the library is also provided. Search in OTL can be achieved through trait ontology category, organ and/or developmental stage, keywords, expression of reporter gene in specific organ/tissue as well as line identification number. OTL now contains the description of 9721 mutant phenotypic traits observed in 2636 lines and 1234 GUS or GFP expression patterns. Each insertion line is documented through a generic passport data including production records, seed stocks and FST information. 8004 and 6101 of the 13 928 lines are characterized by at least one T-DNA and one Tos17 FST, respectively that OTL links to the rice genome browser OryGenesDB.